과밀식재지 밀도관리 및 신규식재지 배식설계 모델 개발 연구 - 화성시 동탄신도시 완충녹지를 대상으로 - 최진우; Choi Jin-woo (한국조경학회지, 2018)
본 연구의 목적은 수목의 과밀생육으로 인한 수형 및 생육불량, 녹지의 기능 저하를 해결하기 위해 과밀식재지의 밀도관리 모델과 신규식재지의 배식설계 모델을 개발하는 것이다. 화성시 동탄신도시의 완충녹지는 도로와 아파트단지사이에 8~15m 폭으로 조성되었다. 완충녹지에 38개의 조사구를 설정하여 조경수 식재패턴 및 생육밀도를 조사하였다. 완충녹지 가로변에는 산딸나무, 복자기, 왕벚나무 등 경관기능의 낙엽활엽수가 67.9% 식재되었다. 마운딩 중앙부에는 스트로브잣나무 71.3%, 상수리나무 9.5%, 아파트변에는 스트로브잣나무 65.9%, 메타세쿼이아 10.2% 등 완충기능의 수목이 주로 식재되었다. 수목의 과밀생육 수준을 효과적으로 평가하기 위해 수관중복률 지표를 개발하여 분석하였다. 과밀생육이 가장 심각한 수종은 스트로브잣나무로 평균 수목밀도 0.3주/m 2 , 평균 수관중복률 35.6%로 매우 높았고, 45% 이상인 지역도 많았다. 수관중복률 지표를 45% 이상(Type A), 30~45%(Type B), 30% 이하(Type C) 등 3단계 척도로 표준화하여 밀도관리 기준을 설정하였다. 생장불량 수목을 우선적으로 관리하는 모델, 식재패턴을 고려하여 유사규격의 수목을 선택하여 관리하는 모델을 제시하였다. 밀도관리 대상수목에 대한 수형 경관성과 이식작업 용이성을 검토하여 이식, 간벌, 가지치기 방법으로 선택할 수 있는 관리방안 적용 체계를 작성하였다. 신규로 조성되는 완충녹지에는 스트로브잣나무의 식재밀도를 0.20~0.25주/m 2 로 완화하는 대신에 관목의 식재밀도를 1.5~2.0주/m 2 로 강화하여 하층을 최소한 30~40% 피복하는 배식설계 모델을 제안하였다. The purpose of this study is to develop a model for the density management of planting sites and an additional model for new planting sites. In the Dongtan New Town of Hwaseong, there are buffer green spaces, with widths between 8m and 15m, between roads and apartment complexes. A total 38 survey plots were set to examine the planting patterns and the density of landscape trees. The Crown Overlapping Index (COI) was developed to assess the level of overcrowding as far as tree growth and development effectively. Pinus strobus recorded the most serious level of overcrowding growth and development. Its average density and average COI were very high at 0.3 trees/㎡ and 35.6%, respectively. There were many areas in which its COI was above 45%. The criteria for density management were set by standardizing the COI into three levels, which were above 45% (Type A), 30~45% (Type B), and under 30% (Type C). A model was proposed to manage poorly growing trees and to develop a model to select and manage trees of similar specification based on the planting patterns. The trees of density management areas were reviewed in terms of tree types and the ease of transplanting to establish an application system for the management plans according to the possibility of transplanting, thinning, and pruning. In new buffer green spaces, the planting density of Pinus strobus was lowered to 0.20~0.25 trees/㎡, with that of shrubs being reduced to 1.5~2.0 trees/㎡, leading to a planting design model to cover the lower parts in at least 30~40%.